ANALISIS EVALUASI DIKLAT PELATIHAN PENGELOLAAN TEKNIS PEMBANGUNAN BANGUNAN GEDUNG NEGARA (STUDI DI BALAI PENGEMBANGAN KOMPETENSI PEKERJAAN UMUM DAN PERUMAHAN RAKYAT (PUPR) WILAYAH VI SURABAYA) - Ratna Sari, Monika; Noviyanti (Jurnal Inovasi Administrasi Negara Terapan (Inovant), 2023)
Education and training (Diklat) is a process which aims to create changes in the attitude/behavior of the target of training. By organizing education and training (diklat) can help the process of developing the competence of an employee to achieve the performance targets of an agency. This study aims to describe the results of the evaluation of training from the implementation of technical management training for the construction of state buildings at the PUPR Region VI Competency Development Center in Surabaya. In this study using the theory of the evaluation model from Daniel L. Stufflebeam which has 4 (indicators) namely Context, Input, Process, Product using descriptive qualitative methods. The research subjects used in this study were training participants and hall employees (staff of the training implementation section and Acting Head of Administration). This research uses primary data sources, namely the results of interviews and secondary data, namely from records, websites, regulations, and other literature data. Data collection techniques using interviews, documentation, and observation and with purposive sampling techniques. Data analysis techniques used are data reduction, data presentation, and conclusion drawing. In this study, the results obtained are: a. context, the purpose of the procurement of technical management training for the construction of state buildings is in accordance with the objectives that have been set or targeted; b. input, the planning of the procurement of this training is in accordance with the objectives/targets set by BPSDM PUPR; c. process, the implementation of technical management training for the construction of state buildings has gone well but some of the implementation processes have shortcomings, namely facilities and infrastructure where e-learing applications sometimes error, unstable internet and wifi networks and poor time management because there are still several learning sessions that are delayed; d. product, participants are able to apply the skills and knowledge they have learned in technical management training for the construction of state buildings, this training has a good/positive impression on participants, and the results of satisfactory scores obtained by participants during the training even though out of 36 participants, this training has a good/positive impression on participants, as well as satisfactory scores obtained by participants during the training even though out of 36 participants. product, participants are able to apply the skills and knowledge they have learned in the training of technical management of the construction of state buildings, this training has a good / positive impression on participants, as well as satisfactory scores obtained by participants during the training even though out of 36 participants there were 3 participants who did not pass.   Keywords: evaluation, education and training, human resources.